Efficacy of induction cisplatin based chemotherapy in locally advanced non small cell lung cancer - Filippazzi, Virginio; Cattaneo, Maria Teresa; Rho, Benedetto; Isa, Luciano; Ferrario, Sabrina; Gambaro, Anna; Tosca, Nicoletta; Isabella, Luigi; Somma, Luisa; Damiani, Eugenia; Veronese, Barbara; Careri, Carmela; et al. (European Journal of Oncology and Environmental Health, 2008)
Background. Data from the literature demonstrate the efficacy of neoadjuvant or induction chemotherapy in eradicating distant micrometastases, of treating patients with good general conditions and increasing the possibility of a complete resection. It offers potential advantages in the management of non small cell lung cancer. Patients and methods. This study evaluated the efficacy and tolerability of neoadjuvant chemotherapy regimens, with two or three drugs, in locally advanced NSCLC patients (pts) From January 2000 65 pts (58 M + 7 F), mean age 60 years, 29 IIIb and 36 IIIa stage were treated with cisplatin-based chemotherapy: 29 pts in combination with vinorelbine (PV), 21 pts in combination with gemcitabine (PG) and 15 pts in combination with epirubicin and vinorelbine (PEV). Results. The overall response rate was 68%, 40 pts (61%) underwent surgical resection, complete tumour resection was achieved in 34 pts and downstaging was observed in 20 pts. The overall median survival was 22 months, while in resected pts it was 28 months; recurrence of disease was observed in 64% of resected pts. A total of 195 cycles of induction chemotherapy were performed with grade III-IV haematological toxicity: 42% neutropenia and 30% anaemia, while emesis and alopecia were in 26% and 37%, respectively. Conclusion. On the basis of our experience induction doublet chemotherapy combinations PV and PG are feasible, tolerable and effective in pts with locally advanced NSCLC, novel triplet regimens such as PEV should be used in selected groups of pts.